PISTA DE NOSSOS MEDOS: (in) segurança viária, mortes e os aspectos negativos da sociabilidade conflituosa no trânsito no município de São Luís – Ma. - LOPES, Anne Caroline Nava (2018)
This thesis deals with the issue of traffic accidents with deaths in the city of. Based on the social relations between individuals in transit situations that are the result of a conflict - generated sociability. It is based on the understanding that traffic accidents involving deaths constitute "epidemics" for current societies and enter the public health agenda with morbimortalities due to external causes, due to the high frequency in which they occur, especially reaching the young / adult. Thus, the issue of road safety, deaths and the negative aspects of conflictive sociability in traffic in the city of São Luís - MA, addressing a critical context of mortality in traffic in the mentioned municipality, which is between the capitals Brazil, leading the ranking of the main regions of the country with an expressive number of deaths. In addition, it depicts an investigation of traffic deaths from the assessment of the negative effects of sociability on the road through the experiences of the victims' families. This is a choice and an important demarcation to understand traffic as a space of disputes that have consequences for the whole of society. This dimension of the work emphasizes the existence of a hierarchy of the social space of transit, that is, realities of deaths intertwined with the question of the inequality between stratified positions of the own society during the conflict and extending to the death. Thus, the general objective of the thesis was to carry out a quanti-quali survey on traffic accidents with deaths in the city of São Luís - MA, in the period from 2010 to 2014. It reiterates that this research has specific objectives: morbidity and mortality in traffic, through documentary and statistical surveys at local, regional, national and global levels; To analyze the socioeconomic characteristics of the relatives of fatal victims and to know the impacts of this type of death among different social classes; To identify elements present in the narratives of the relatives of the victims of fatal traffic accidents in the city of São Luís - MA, traces of the relationship of traffic with death. We conclude for what we consider a "class struggle" in the transit environment, where individuals of distinct social and hierarchical positions meet and keep alive the terrible dispute over space.